Autobiography, Travel and Postnational Identity - Majeed, Javed. author. aut Link
VI, 309 p.
Keywords: This book examines concepts of travel in the autobiographies of leading Indian nationalists in order to show how nationalism is grounded in notions of individual selfhood, and how the writing of autobiography, fused with the genre of the travelogue, played a key role in formulating the complex tie between interiority and nationality in South Asia.